2018
DOI: 10.2196/humanfactors.9049
|View full text |Cite
|
Sign up to set email alerts
|

Human Factors and Data Logging Processes With the Use of Advanced Technology for Adults With Type 1 Diabetes: Systematic Integrative Review

Abstract: BackgroundPeople with type 1 diabetes (T1D) undertake self-management to prevent short and long-term complications. Advanced technology potentially supports such activities but requires consideration of psychological and behavioral constructs and usability issues. Economic factors and health care provider capacity influence access and uptake of advanced technology. Previous reviews have focused upon clinical outcomes or were descriptive or have synthesized studies on adults with those on children and young peo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 42 publications
(72 reference statements)
0
11
0
2
Order By: Relevance
“…Mobile phone apps are widely used in both developed and developing countries and have shown great potential to deliver personalized medical advice. In prior studies, apps were demonstrated to facilitate patients’ health promotion by improving their self-management awareness and compliance [7-9]. In practice, apps have been used to help people living with various health conditions and problems, including mental health [10,11], heart failure [12], and smoking cessation [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Mobile phone apps are widely used in both developed and developing countries and have shown great potential to deliver personalized medical advice. In prior studies, apps were demonstrated to facilitate patients’ health promotion by improving their self-management awareness and compliance [7-9]. In practice, apps have been used to help people living with various health conditions and problems, including mental health [10,11], heart failure [12], and smoking cessation [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Constantly wearing a diabetes device on one's body may negatively impact body image in select individuals . Body image concerns seem to substantially impact the user's attitude towards visibly worn diabetes technologies .…”
Section: What Has the Past 25 Years Of Research Told Us?mentioning
confidence: 99%
“…Впоследствии позитивное влияние НМГ на психологическое благополучие неоднократно подтверждалось. Так, в представительном аналитическом обзоре Waite отмечается, что использование ППИИ в сочетании с НМГ более позитивно влияет на КЖ, чем только ППИИ [42]. Указанная закономерность справедлива не только для НМГ в сочетании с ППИИ.…”
Section: непрерывное мониторирование гликемииunclassified
“…В нем предпринята попытка структурирования ряда исследований в данной сфере, выделения ключевых не биомедицинских аспектов, связанных с использованием новых технологий, прежде всего ППИИ и НМГ. Авторы полагают, что их можно свести к следующим четырем блокам [42]: 1) поведенческий (барьеры приверженности; требования технологий, которые могут влиять на мотивацию ежедневного управления устройствами; время, затрачиваемое на лечение СД); 2) психологический (адаптация к СД; страх гипогликемии; эмоциональная нагрузка, обусловленная ответственностью за самостоятельное управление СД; вера в себя, влияние на КЖ, бессознательные мотивы; доверие технологии; депрессия и расстройства приема пищи; 3) социальный (удобство ношения устройства и образ тела; отношения с окружающими и выработка способов взаимодействия с ними; поддержка пациента его окружением в использовании технологий; выбор того, с кем можно поделиться результатами; стигматизация, связанная с использованием технологии в повседневных условиях); 4) когнитивный (образовательные нужды, в т.ч. обучение технологии и улучшение понимания того, как адаптировать дозы; дополнительное обучение, ассоциированное с использованием технологии; грамотность в отношении здоровья; обусловленное возрастом и образованием снижение когнитивных способностей).…”
Section: непрерывное мониторирование гликемииunclassified